The Maritime Industry of Nigeria. Challenges and Sustainable Prospects: Array - Faith, Alari Emomoemi (Danubius Working Papers, 2020)
In this paper, we have analysed the history of the Nigerian Shipping Industry in mid-1950s, Nigeria’s first indigenous shipping line the “Nigerian Line” was established by Mr. Patrick Osoba as a joint venture with the Finnish firm, Nordstrom and Company. Furthermore, the evolution of the Nigerian fleet will be shown in statistics from 1980 to 2017 and what happened between these years. There are many challenges that affects the Maritime Transportation Industry in Nigeria and these have to be solved and taken into consideration because this Industry plays a vital role in the Economy and growth of the Nation. These challenges are funding, manpower, legislation, pollution, safety etc. these would be expatiated further into this paper, and we have tried to analyze these challenges, giving a proposal on how to boost the Nigerian Maritime Industry.